Species delimitation of colour polymorphic Cladophorus (Coleoptera: Lycidae) from New Guinea - Kalousova, Romana; Bocak, Ladislav (Zootaxa, 2017)
Cladophorus Guérin-Méneville, 1830 are endemic Papuan net-winged beetles which take part in highly diverse Müllerian mimicry rings. Available specimens were sequenced for cox1–tRNA-Leu–cox2 mitochondrial DNA fragment and the species delimitations were based on the genetic distance, phylogenetic analysis, and morphology. Three earlier described species were identified in the recently collected material and further 10 species are described: C. pallescens sp. nov., C. bicolor sp. nov., C. craterensis sp. nov., C. motykai sp. nov., C. mindikensis sp. nov., C. kailakiensis sp. nov., C. manokwarensis sp. nov., C. haiaensis sp. nov., C. humeralis sp. nov., and C. boceki sp. nov. DNA-based identifications provided some ambiguous results and closely related species could not be robustly delimited using solely molecular data. Additionally, the species limits were based on clearly defined morphological characters and the morphological differentiation was found unlinked from the genetic divergence. Colour patterns cannot be used for identification because all species available in more specimens were polymorphic and followed various local co-mimics. The Papuan fauna of Cladophorus is very diverse and the closely related species regularly occur in limited regions. Differentiation within restricted ranges is therefore considered as the main speciation mode.